Towards A New Era of Maritime Transformation with A Blue Economy: Meta-Synthesis - Sain, Muhammad (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research investigates the transformation of the blue economy and its contribution to long-term sustainability and prosperity. Using a literature analysis approach, this research identifies key factors that influence the success of blue economy transformation, such as adaptive governance policies, multi-stakeholder participation, and paradigm shifts in marine resource management. The research results also highlight the important role of stakeholders such as government, the private sector and local communities in promoting a sustainable blue economy. In addition, this research identifies the challenges that may be faced, such as poor governance and limited funding , and emphasizes the importance of technological innovation and investment in supporting blue economy transformation. By providing a comprehensive framework, this research has the potential to assist policymakers and stakeholders in designing strategies to realize a sustainable and inclusive blue economy.